Ocular manifestations in patients with corona virus disease (COVID-19) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Corona virus disease (COVID-19) has affected many subspecialties including ophthalmology. We aimed to determine the ocular manifestations of COVID-19 patients treated in a dedicated tertiary care hospital, in Nepal.Method: This was a descriptive cross-sectional study in hospitalized COVID-19 patients in Patan Hospital, Patan Academy of Health Sciences, Kathmandu, Nepal. Data were collected during 6 months from November 2020 to May 2021 to achieve a for a specified sample size of 90. Ophthalmological manifestations were recorded in the consenting participants. Ethical approval was obtained.Result: One or more ocular manifestations were seen in 3.4% of admitted COVID-19 patients. Bilateral diffuse red eyes was the most common manifestation.Conclusion: Bilateral diffuse red eye was the common ocular manifestation in admitted COVID-19 patients.